Cognitive Bias in Usability Testing. Issue 1 (June 2016) - Natesan, Divya; Walker, Morgan; Clark, Shannon
Cognitive bias is the tendency to subconsciously change ones actions or thought process based on someone else's comments or behavior. It is important to consider cognitive bias when performing a usability study because it can significantly alter or impair the validity of the results. While cognitive bias cannot always be entirely eliminated, identifying key cognitive biases to which usability study results are particularly susceptible is the first step to mitigating them. Once experimenters are alert to these subtle traps, they can consider approaches that sidestep the biases and greatly improve the accuracy and overall effectiveness of a usability study.